2020
DOI: 10.1364/oe.28.010294
|View full text |Cite
|
Sign up to set email alerts
|

Nonradiating anapole condition derived from Devaney-Wolf theorem and excited in a broken-symmetry dielectric particle

Abstract: In this work, we first derive the nonradiating anapole condition with a straightforward theoretical demonstration exploiting one of the Devaney-Wolf theorems for nonradiating currents. Based on the equivalent volumetric and surface electromagnetic sources, it is possible to establish a unique compact conditions directly from Maxwell’s Equations in order to ensure nonradiating anapole state. In addition, we support our theoretical findings with a numerical investigation on a broken-symmetry dielectric particle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…This circulating magnetic moment M , accompanied by the electric poloidal current, formed a strong toroidal dipole moment T. As shown in Figure g, in general, the symmetry of the radiation patterns of the electric dipole P and toroidal dipole T modes is similar. Thus, the strongly induced electric toroidal dipole inside the silicon disk leads to total scattering cancelation in the far field through destructive interference with electric dipole radiation, resulting in an anapole state. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This circulating magnetic moment M , accompanied by the electric poloidal current, formed a strong toroidal dipole moment T. As shown in Figure g, in general, the symmetry of the radiation patterns of the electric dipole P and toroidal dipole T modes is similar. Thus, the strongly induced electric toroidal dipole inside the silicon disk leads to total scattering cancelation in the far field through destructive interference with electric dipole radiation, resulting in an anapole state. ,, …”
Section: Resultsmentioning
confidence: 99%
“…To address this shortcoming, various Mie resonators with high-index dielectric nanostructures have recently been proposed as promising alternatives for manipulating light at the nanoscale. Among the scattering Mie resonance modes, the anapole mode provides an enhanced near-electric field but suppresses far-field excitations, and thus far, it has been successfully applied in strong coupling effects, surface-enhanced Raman scattering, and biosensing applications. Nevertheless, we always obtained a relatively mild field enhancement effect in conventional anapole systems. Herein, for the purpose of high-efficiency light traps in a wide range of optical frequencies and efficient light–matter interactions, we theoretically designed a hybrid anapole system composed of a nanohole silicon disk and an LBDP mode-supported gold dimer disk. We then demonstrated that the anapole mode originates from the LBDP mode of the dimer disk’s destructive interference with the toroidal dipole moment.…”
Section: Introductionmentioning
confidence: 99%
“…0 ensures that F is nonradiating field and source has nonradiating current J NR [31]. The equivalent current J eq that is generated by the anapole metamolecule must obey the following expression and tends to zero [32]:…”
Section: Pseudo-anapole Statementioning
confidence: 99%
“…[ 10–13 ] In addition, owing to the identical scattering patterns between toroidal and electric dipoles, when these two dipoles have the same amplitude but are out of phase, the complete destructive interference between toroidal and electric dipolar emission results in the so‐called “anapole mode” with radiationless property. [ 14–17 ] The unusual subradiating characteristic of the anapole mode accompanied with highly electromagnetic field confinement in subwavelength structures thus gives rise to enhanced nonlinear effects, [ 18–22 ] nontrivial resonant transparency, [ 23–25 ] as well as low‐threshold lasing. [ 7,26 ]…”
Section: Introductionmentioning
confidence: 99%